Analisis Pengaruh Iklan Aplikasi Bibit Reksadana dan Literasi Keuangan Terhadap Keputusan Investasi Bagi Masyarakat Kota Bojonegoro - Nadia Kusuma Rahmawati; Retno Muslinawati; Dados Susilowati (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2023)
Individual financial conditions have a major influence on human survival. Low wage rates can be one of the causes of financial problems. Seeing the low level of wages in Bojonegoro City, it is necessary to have knowledge about how to manage good sources of income. One way to do good financial management is to invest.. Bibit mutual fund application is one of the investment media whose advertisements appear on social media. Thus the purpose of this study is to determine the effect of mutual fund seed advertisements, financial literacy, and personal interest on the investment decisions of the people of Bojonegoro City. Sampling in this study used a nonprobability sampling method with a Snowball sampling approach. The results show that Bibit advertising, financial literacy, and personal interest influence investment decisions.